2019
DOI: 10.12973/eu-jer.8.3.875
|View full text |Cite
|
Sign up to set email alerts
|

Gamification as a Tool for Stimulating the Educational Activity of Students of Higher Educational Institutions of Ukraine and the United States

Iryna Zvarych,
Svitlana M. Kalaur,
Nataliya M. Prymachenko
et al.

Abstract: This study has experimentally tested how the introduction of simulations, adapting the experience of higher educational institutions of the United States, including the elements of gamification, in the training course Professional Foreign Language stimulates the educational activity of students at higher educational institutions of Ukraine students' educational activity through the involvement and creation of activity for constructive competition and cooperation, stimulation of interests and motives, maintaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
0
13
0
2
Order By: Relevance
“…Thus, Marcus et al (Marcus et al, 2018) disclosed ways to use feature films in the teaching of history. D. Wong et al (Wong et al, 2007) considered the new role of a teacher as a film maker and technology for its implementation. Zvarych et al (Zvarych et al, 2019) showed that gamification can not only lead to gaming addiction, but also increase the educational motivation of students, as evidenced by studies conducted in universities in the USA and Ukraine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Marcus et al (Marcus et al, 2018) disclosed ways to use feature films in the teaching of history. D. Wong et al (Wong et al, 2007) considered the new role of a teacher as a film maker and technology for its implementation. Zvarych et al (Zvarych et al, 2019) showed that gamification can not only lead to gaming addiction, but also increase the educational motivation of students, as evidenced by studies conducted in universities in the USA and Ukraine.…”
Section: Discussionmentioning
confidence: 99%
“…D. Wong et al (Wong et al, 2007) considered the new role of a teacher as a film maker and technology for its implementation. Zvarych et al (Zvarych et al, 2019) showed that gamification can not only lead to gaming addiction, but also increase the educational motivation of students, as evidenced by studies conducted in universities in the USA and Ukraine. E. Camarero and D. Varona (Camarero, Varona, 2016) considered increased media literacy as a factor in positive social changes.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the scientific works (Dubych, 2016;Soroka et al, 2019;Thu, 2014;Zvarych et al, 2019) shows that there are two groups of methods of evaluation of corporate culture -qualitative -typology of Moran, Harris, and Routledge (2007), Shain (2001), Wu (2008) -and quantitative. In contrast to the qualitative ones, which although allow to obtain a clear result of the study and to identify the characteristics of culture, they have a drawback of inability to reveal the in-depth features of the corporate culture.…”
Section: Methodsmentioning
confidence: 99%
“…One of the organizational subsystems (technological and administrative) that performs the function of adaptation of the organization to the environment and identification of its employees; a set of attitudes, symbols, rituals and myths that serve the interests of the organization and each employee, transferred from mouth to mouth as a life experience (Lipatov, 1997) Lipatov (1997 A set of assumptions, beliefs, values and norms that are endorsed by all members of the organization that contribute to its competitiveness (Zhogan & Savchuk, 2009) Zhogan and Savchuk (2009) "A set of basic provisions, formed independently, learned or developed by a certain group, as it learns to solve the problems of adaptation to the external environment and internal integration, which proved to be effective enough to be considered valuable, and therefore transferred to new members as the correct way of acceptance, thinking and attitude to specific problems" (Shain, 2001) Shain 2001A specific form of existence of system interdependence, which includes a hierarchy of values that dominate among the employees of the organization, and a set of ways to implement them, prevailing in it at a certain stage of development (Chernyshova & Nemchenko, 2010 One of the ways to carry out organizational activity through the use of language, folklore, traditions and other means of transmission of basic values, beliefs, ideologies (Morgan, 1986) Morgan (1986 So, as you can see from the data in table. 2, most authors note that corporate culture is a system, some argue that it is a specific form, a set of provisions or means.…”
Section: Semykina (2013)mentioning
confidence: 99%
“…Scientific and practical interest in cluster subject is increasing in Ukraine (Ukraine Education Cluster, 2019) and Europe (European Commission, 2019;National Research Council, 2011). Among the scientific works, studies by Kusyk (2010), Lenchuk and Vlaskin (2010), Piatnytska (2016), Chernyshova (2012) and Zvarych et al (2019) are of interest in the context of our study, which analyzed the categorically conceptual framework, as well as economic and social nature of clusters, problems of their implementation, principles and effectiveness of their functioning, development and experience of their support by the state. However, the tools to be used by clusters for improving the professional competence of future educators remain unexplored.…”
Section: Introductionmentioning
confidence: 99%